2018
DOI: 10.1002/ange.201811099
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doped Carbon–CoOx Nanohybrids: A Precious Metal Free Cathode that Exceeds 1.0 W cm−2 Peak Power and 100 h Life in Anion‐Exchange Membrane Fuel Cells

Abstract: Efficient and durable nonprecious metal electrocatalysts for the oxygen reduction (ORR) are highly desirable for several electrochemical devices,i ncluding anion exchange membrane fuel cells (AEMFCs). Here,a2D planar electrocatalyst with CoO x embedded in nitrogen-doped graphitic carbon (N-C-CoO x )was created through the direct pyrolysis of am etal-organic complex with aN aCl template.T he N-C-CoO x catalyst showed high ORR activity,indicated by excellent half-wave (0.84 Vv s. RHE) and onset (1.01 Vv s. RHE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…On the other hand, compared to the state-of-the-art polyaromatics-based AEMFCs (<2.08 W cm −2 in H 2 –O 2 with 2.0/2.0 bar back pressure) 17 , 32 , 34 , our present AEMFCs showed higher PPDs. Note that GT- x series and BTMA-HDPE-based AEMFCs employed a high Pt–Ru/C loading of 0.7 mg cm −2 , while the present PFAP-based cells exhibited high performance with a low PGM loading of 0.33–0.42 mg cm −2 44 , 45 .…”
Section: Resultsmentioning
confidence: 76%
“…On the other hand, compared to the state-of-the-art polyaromatics-based AEMFCs (<2.08 W cm −2 in H 2 –O 2 with 2.0/2.0 bar back pressure) 17 , 32 , 34 , our present AEMFCs showed higher PPDs. Note that GT- x series and BTMA-HDPE-based AEMFCs employed a high Pt–Ru/C loading of 0.7 mg cm −2 , while the present PFAP-based cells exhibited high performance with a low PGM loading of 0.33–0.42 mg cm −2 44 , 45 .…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, Hou et al [143] reported N-, B-codoped graphitic carbon nanocage (NB-CN) with defect-rich property, which is a promising trifunctional electrocatalyst for ORR, OER, and HER. Furthermore, the P/N [73,82,125], O/N [114]-codoped, P/S/N [150,151]-tridoped porous nanocarbons with abundant edges or defects have been widely employed as the bi-or trifunctional nanocarbon electrocatalysts for ORR, OER, and HER. These results demonstrated that the co-engineering of heteroatom doping and defect inducing is a general strategy for the enhancement of the electrocatalytic activities for nanocarbon.…”
Section: Defects Coupled With Multi Dopantsmentioning
confidence: 99%
“…[13][14] Several recent research papers have also reported promising replacement of PGM-by PGM-free cathodes reaching peak powers > 1 W cm −2 . [15][16] Furthermore, continuous progress in membrane development has drastically increased the initial power performance of AEM-FC, now at par or even higher than that reached with PEM-FCs, at a comparable total PGM loading in the entire membrane-electrode-assemblies. [17][18] This advantage could lead to a significant reduction in the cost of FC technology if PGM loading at the anode of AEM-FC can be significantly reduced or zeroed in the future.…”
Section: Introductionmentioning
confidence: 99%